Plasma physics: an introductory course - Dendy, Richard (Cambridge: Cambridge University Press, 1993)
This book covers the subject of plasma physics. The first few chapters deal with the fundamentals of plasma physics. Subsequently, the applications and properties of human-made and naturally occurring plasmas are discussed. In addition, there are chapters devoted to general phenomena, such as turbulence and chaos. The computational techniques employed in modeling plasma behavior are also described.
Includes bibliographical references.; Index 509-513p.
Keywords: Ionized gases; Plasma physics; Physics